Influence of relaxation on the deployment behaviour of a CFRP composite elastic–hinge. (1st March 2021) - Fernandes, P.; Sousa, B.; Marques, R.; Tavares, João Manuel R.S.; Marques, A.T.; Jorge, R.M. Natal; Pinto, R.; Correia, N.
Abstract: Deployable structures are an interesting option to replace mechanical systems in space applications, allowing a more efficient use of the limited space available for the payload. However, due to the probability of long stowage times in a retracted configuration, composite deployable structures are prone to suffer some type of relaxation phenomenon, which may compromise the deployment. This research describes how to implement a technique to assess the characterization of the relaxation behaviour of a material certified for space applications and its influence in the opening of a deployable elastic–hinge. The relaxation master curve of the material was determined using an accelerated experimental testing technique where temperature is used to promote accelerated ageing in the material. This data was then introduced in a finite element model. Finite element analysis was used to predict the deployment behaviour of the structure before and after the influence of material relaxation due to the stowage of the elastic–hinge for a certain period of time, using the relaxation master curve. The relaxation of the material led to an increase in the time necessary to complete the deployment. This is due to a significant reduction in the internal energy of the elastic–hinge.